Creation and Ideology: from Freedom of Opinions to "Cancel Culture" - Crișan, Sorin (Theatrical Research, 2022)
The space of cultural and language exchange (of speech, opinions, etc.) has entered a new phase which is authoritatively dominated by everything that is carried by the new and vastly adopted cultural and ideo- logical movement of African American origins, referred to as “Cancel Culture”. This movement – an extension of the previous movement, the “callout culture”, in other words, the culture of cancellation, neutralization, refusal or interdiction – sets the mission of a new conformism, becoming a controversial and polarizing topic of discussion. The phrase, borrowed from the rappers and already used in all media, hardly receives an equivalent in Romanian, becoming and echoing a type of totalitarian censorship – which I believed we got rid of – that, unfortunately, is not a simple trend adopted by the followers of Progressivism and, thus, that is not going to go away any soon.